Exploring the cause of aggregation and reduced Zn binding affinity by G85R mutation in SOD1 rendering amyotrophic lateral sclerosis. Issue 7 (7th April 2017) - Srinivasan, E.; Rajasekaran, R.
ABSTRACT: Amyotrophic lateral sclerosis (ALS), a lethal neurodegenerative disorder is characterized by the degeneration of upper and lower motor neuron. ALS occurs due to various notably prominent missense mutations, in gene encoding Cu‐Zn superoxide dismutase (SOD1) thereby leading to aggregation, dysfunction and reduced Zn binding affinity. In this study, one such mutation, G85R was explored in comparison with wild type SOD1, using discrete molecular dynamics (DMD). Accordingly, the conformational changes were significantly observed in mutant SOD1, through various geometrical parameters, which substantiated the difference in conformational deviation, flexibility and compactness, thus stipulating a root cause for aggregation. Followed by, analysis of essential dynamics further authenticated the cause behind the protein dysfunction. In particular, the high content of beta sheet with structural deviations, down to dysfunction was established in mutant as compared to wild type, while passing through secondary structure analysis. Subsequently, the deviation of distance in Zn binding residues was distinctly portrayed in mutant as compared to wild type, thus confirming the cause of reduced Zn binding affinity. In addition, the steered molecular dynamics analysis also authenticated the above results indicating the reduced Zn binding affinity in the mutant as compared to that of the wild type. Hence, this work revealed the theoretical mechanism to unravel the mutational effects of cofactor dependent protein. Proteins 2017; 85:1276–1286. © 2017 Wiley Periodicals, Inc.